2017
DOI: 10.1136/archdischild-2017-312848
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough postacute respiratory illness in children: a cohort study

Abstract: When chronic cough develops post-ARI, clinical review is warranted, particularly if parents report a history of prolonged or recurrent cough. Parents of children presenting acutely to ED with cough should be counselled about the development of chronic cough, as an underlying respiratory condition is not uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
4
40
0
3
Order By: Relevance
“…Blood and nasopharyngeal aspirate (NPA) were tested for bacteria via PCR for Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Bordetella pertussis, Mycoplasma pneumoniae , and Chlamydophila pneumoniae . Moraxella catarrhalis was considered a significant pathogen if induced sputum culture had a pure growth of Moraxella catarrhalis , that is, in the presence of epithelial cells: pus cell <1:10 . Chest radiographs were reviewed by a designated radiologist who was blinded to the signs and symptoms of the patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood and nasopharyngeal aspirate (NPA) were tested for bacteria via PCR for Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Bordetella pertussis, Mycoplasma pneumoniae , and Chlamydophila pneumoniae . Moraxella catarrhalis was considered a significant pathogen if induced sputum culture had a pure growth of Moraxella catarrhalis , that is, in the presence of epithelial cells: pus cell <1:10 . Chest radiographs were reviewed by a designated radiologist who was blinded to the signs and symptoms of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…During admission for their LRTI, induced sputum 18 19,20 Chest radiographs were reviewed by a designated radiologist who was blinded to the signs and symptoms of the patient.…”
Section: Specimen Collection and Analysismentioning
confidence: 99%
“…A study of 93 children with persistent cough and bronchiectasis found that the duration of the cough correlated with severity markers for bronchiectasis . Children with episodes of recurrent pneumonia, recurrent prolonged bacterial bronchitis or a cough that is not responsive to a prolonged (more than 4 weeks) course of antibiotics should also be considered for an underlying diagnosis of bronchiectasis . In addition, children investigated for asthma in whom symptoms do not improve with treatment should be investigated for bronchiectasis, especially those presenting with cough variant asthma.…”
Section: Diagnosismentioning
confidence: 99%
“…Any daily, chronic, productive-sounding cough should raise the suspicion of an underlying cause, especially if the child is ill or has other worrying features 30. British Thoracic Society guidelines define chronic cough as cough lasting more than eight weeks,31 whereas other documents define it as lasting more than four weeks,32 neither figure being evidence based.…”
Section: How To Make a Diagnosis?mentioning
confidence: 99%